2015
DOI: 10.15850/amj.v2n4.658
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Allergic Rhinitis based on World Health Organization (ARIA-WHO) questionnaire among Batch 2010 Students of the Faculty of Medicine Universitas Padjadjaran

Abstract: Background: Allergic rhinitis (AR) is a common disease affecting 5-45% of Asian population. Although it is not a life-threatening disease, AR significantly hampers the quality of life of the sufferers. The prevalence of AR among adults in Indonesia is still unknown. This study aimed to measure the prevalence of AR among batch 2010 students of the Faculty of Medicine, Universitas Padjadjaran. Methods: A cross-sectional study was conducted during June-October 2013 involving Indonesian class batch 2010 students o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
2
8
0
4
Order By: Relevance
“…The number of female RAS patients was higher than the number of male patients in this study, as in previous studies [19,20]. In this study we also found that women suffer from RAS and have allergic rhinitis (AR) more often than men, which is consistent with data that AR is often found in women and in the age range of 10-29 years [21]. Allergic rhinitis (AR) is a common disorder of the nose.…”
Section: Discussionsupporting
confidence: 92%
“…The number of female RAS patients was higher than the number of male patients in this study, as in previous studies [19,20]. In this study we also found that women suffer from RAS and have allergic rhinitis (AR) more often than men, which is consistent with data that AR is often found in women and in the age range of 10-29 years [21]. Allergic rhinitis (AR) is a common disorder of the nose.…”
Section: Discussionsupporting
confidence: 92%
“…Ada banyak faktor etiologi dan predisposisi yang dapat menyebabkan terjadinya rinosinusitis kronik antara lain adalah ISPA akibat virus, berbagai macam jenis rinitis terutama rinitis alergi, polip hidung, kelainan struktur anatomi seperti deviasi septum atau hipertrofi konka dan sumbatan pada ostio-meatal kompleks (KOM) (Mangunkusumo et al, 2016). Berdasarkan survey yang dilakukan oleh World Health Organization (WHO), pada tahun 2011 diperkirakan sekitar 400 juta orang di dunia menderita rinitis alergi Pada tahun 2015 sebanyak 64 % dari pasien rinitis alergi yang mengunjungi departemen otolaringologi -kepala dan bedah leher di Rumah Sakit Hasan Sadikin Bandung (Fauzi, 2015). Saat ini di RSUD A. Dadi Tjokrodipo Bandar Lampung, Rinosinusitis kronis merupakan salah satu penyakit yang sering dijumpai di poli THT RSUD A. Dadi Tjokrodipo Bandar Lampung.…”
Section: Pendahuluanunclassified
“…2 Prevalensi rinitis alergi pada anak di Medan Barat adalah 51,3% dan pada mahasiswa sebesar 38,2%. 3,4 Prevalensi rinitis pada anak usia 13-14 tahun di Jakarta Barat tahun 2008 adalah 16,4% dan di Ciputat Timur, Tangerang, sebesar 25,20%. 5,6 Penyakit ini mengganggu kualitas hidup penderitanya karena bersifat kronik.…”
Section: Pendahuluanunclassified